Evaluation of Crude Extract of Melia azedarach Linn. Against Attenuated Amphotericin B Resistant Leishmania tropica Strain - Imran Khan; Muhammad Naveed Umar (Journal of Basic & Applied Sciences, 2015)
Cutaneous leishmaniasis is still a big health problem around the world and drug resistance has emerged as a major problem in treatment. The purpose of the study was to generate Amphotericin B resistant strainand evaluate the crude extract of Melia azedarach against wild and lab generated resistant strain of Leishmania tropica. The result obtained revealed that the continuous increase of drug pressure for 60 days cause resistance in L. tropica by 09 fold compared to wild type. The LC50 value recorded for wild and resistant type strain was 0.024 and 0.224µg/ml, respectively against Amp B drug. The antileishmanial activity of crude extract against wild and resistant type strain was 0.57 and 123.3 µg/ml for green fruit and 1220.8 and 4010.1µg/ml for ripe fruit, respectively. A significant difference (P<0.05) in activitieswere observed between green and ripe fruit against wild and resistant type of strain. Based on the results obtained, it can be concluded that green fruit show promising results against resistant type of L. tropica and could be a novel candidate for anti-protozoal activity.